SISTEM INFORMASI UNTUK MENENTUKAN PENERIMAAN BANTUAN PROGRAM KELUARGA HARAPAN DI KELURAHAN PASAR MERAH TIMUR - Silvira Fajar Yanti; Yuyun Dwi Lestari; Dodi Hidayat (Politeknik Bisnis Indonesia, 2022)
The Family Hope Program (PKH) is a social assistance program for underprivileged and vulnerable families by the Ministry of Social Affairs of the Republic of Indonesia with various conditions. This program aims to help the poor as well as a mechanism for social protection and poverty alleviation. The selection process that took place at the Pasar Merah Timur Kelurahan office still had several drawbacks, because the selection process was still manual and there was an element of subjectivity in determining potential PKH beneficiaries, this would result in PKH beneficiaries not being on target. To solve this problem, a web-based information system for determining Family Hope Program Assistance (PKH) was designed. The existence of this web-based system can help make it easier to determine the PKH assistance process using the information system.